Introduction to molecular thermodynamics - Hanson, Robert M. 1957-; Green, Susan M. E. 1971- (University of Science Books, 2008)
Starting with just a few basic principles of probabilityand the distribution of energy, this book takes students (and faculty!) on anadventure into the inner workings of the molecular world like no other